Kecemasan Nomophobia pada Mahasiswa: Bagaimanakah Peranan Kontrol Diri? - Ariska, Amanda Devina; Sukiatni, Dwi Sarwindah; Kusumandari, Rahma (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
In the modern era like today, the sophistication of technology in smartphones is currently growing rapidly compared to before. Because smartphones in the current era make it easy for users to access anything easily. This is what makes humans dependent on the existence of smartphones, especially students who often feel anxious when they are away from their smartphones. This phenomenon is called nomophobia anxiety. 1) Nomophobia anxiety is a feeling of anxiety and fear when individuals are away from their smartphones. 2) This study aims to determine the relationship between self-control and nomophobia anxiety in college students. 3) The population in the study was 12,361 active students at the university of August 17 1945 Surabaya with a research sample of 288 students. This research data collection technique uses incidental sampling techniques. 4) Data collection from the results of the self- control scale and nomophobia anxiety scale, each of which consists of 21 items with an α =0.837 value and 29 items with an α =0.906 value. The data analysis used is a simple analysis which shows rxy = -575 at p = 0.00 (<0.05) 5) meaning that there is a significant negative relationship between the two variables.